La dinámica local-global de la circulación del conocimiento en una facultad de ciencias bioquímicas de una universidad pública argentina: aportes para repensar los sistemas de evaluación científica en América Latina - Larisa Cybulski; Gabriela Isuani; Andrés A. Sciara; Fernando Díaz Pacífico; Nahuel Pallitto; Fernanda Beigel (INTER DISCIPLINA, 2026)
Since the establishment of the Science Citation Index in the 1960s, scientific evaluation systems have favored metrics like the impact factor (IF), creating a hierarchy that privileges “mainstream” journals while marginalizing local publications. This model has driven Latin American researchers to publish in international journals, often in English and with high article processing charges (APCs), to gain academic recognition and funding. However, this dynamic has undervalued regional journals, despite initiatives like SciELO, RedALyC, and Latindex demonstrating high standards of quality, open access, and increasing internationalization. In response, an interdisciplinary team proposed the creation of a local scientific journal at the Faculty of Biochemical and Pharmaceutical Sciences of the National University of Rosario (FBIOyF, by its Spanish acronym), aiming to engage globally without neglecting local values and criteria. To assess this initiative, we conducted a survey among faculty researchers. The results reveal significant interest in a publication that promotes the dissemination of locally generated knowledge, facilitates access for non-English-speaking communities, and fosters interdisciplinary collaborations, making science more equitable and more sensitive to social context.